Career satisfaction and future intentions in the hospitality industry: an intrinsic or an extrinsic proposition? - Zopiatis, Anastasios; Theocharous, Antonis L.; Constanti, Panayiotis (My University, 2018)
Job satisfaction is probably one of the most researched topics in the hospitality literature and, whereas career satisfaction, defined as the gratification with the accumulation of career-related experiences over time, has received much less attention. With the intention of enhancing our conceptual understanding and adding to this discourse, this study aims to investigate the effects of both intrinsic and extrinsic job traits on the individual's career satisfaction and subsequent intention to remain in the hospitality industry. The study investigates individuals working as full time employees in hotel establishments in Cyprus. Findings, some of which challenge existing theoretical paradigms, are of interest to stakeholders both in the industry and the academic community.
Keywords: Career satisfaction; Cyprus; Extrinsic traits; Hospitality industry; Intrinsic traits